Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/mrm.26084
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control design of turbo spin‐echo sequences with applications to parallel‐transmit systems

Abstract: PurposeThe design of turbo spin‐echo sequences is modeled as a dynamic optimization problem which includes the case of inhomogeneous transmit radiofrequency fields. This problem is efficiently solved by optimal control techniques making it possible to design patient‐specific sequences online.Theory and MethodsThe extended phase graph formalism is employed to model the signal evolution. The design problem is cast as an optimal control problem and an efficient numerical procedure for its solution is given. The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 35 publications
(79 reference statements)
0
33
0
Order By: Relevance
“…When using systems with parallel transmission capability, the extra degree of freedom offered by the long refocusing pulse trains, allows dynamic adaptation of the rf-shimming associated with each refocusing pulse in order to ensure a homogeneous contrast (Sbrizzi et al, 2016). When performing 3D acquisitions in the sagittal orientation (readout in the head foot direction), the freedom gained from the possibility of not needing spatially selective RF pulses for whole brain imaging, can be exploited to apply short 3D tailored non-selective pulses, kT points (Cloos et al, 2012), for both the excitation and refocusing pulses to obtain a more homogeneous contrast throughout the brain either in combination with (Eggenschwiler et al, 2014;Massire et al, 2015) or without (Eggenschwiler et al, 2016)parallel transmission.…”
Section: Fast Spin Echo and Grasementioning
confidence: 99%
“…When using systems with parallel transmission capability, the extra degree of freedom offered by the long refocusing pulse trains, allows dynamic adaptation of the rf-shimming associated with each refocusing pulse in order to ensure a homogeneous contrast (Sbrizzi et al, 2016). When performing 3D acquisitions in the sagittal orientation (readout in the head foot direction), the freedom gained from the possibility of not needing spatially selective RF pulses for whole brain imaging, can be exploited to apply short 3D tailored non-selective pulses, kT points (Cloos et al, 2012), for both the excitation and refocusing pulses to obtain a more homogeneous contrast throughout the brain either in combination with (Eggenschwiler et al, 2014;Massire et al, 2015) or without (Eggenschwiler et al, 2016)parallel transmission.…”
Section: Fast Spin Echo and Grasementioning
confidence: 99%
“…In previous works, the pulses along the train were designed individually using an optimal control approach . Sbrizzi et al also proposed a signal‐based approach to design the refocusing RF pulses, thereby relaxing the CPMG condition. Clearly, given the large amount of degrees of freedom allowed by optimal control approaches, excellent performance can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, any change in the nominal signal evolution indeed would require a new pulse optimization. In addition, in and , separately designed refocusing RF pulses lead to greater RF pulse design complexity and typically require some heuristics to take into account hardware and safety (local and global SAR) limits. In comparison, for the SPACE sequence investigated in this work, a single pulse was designed.…”
Section: Discussionmentioning
confidence: 99%
“…The DSC algorithm can in principle compute separate optimized RF shim settings (for the 8‐channel transmit coil) for each of the 192 pulses in the echo train; however, the cost is that each element of w (192 × 8 complex matrix) must be computed. In previous work, it was shown that good results may be achieved by reducing the number of degrees of freedom by applying a mapping w'=bold-italicP1w, for which w′ is a matrix of size Ns×Nc; Ns is a smaller number of independent RF shim settings; and P is a mapping matrix. In this work, we set N s = 16 and mapped the first 13 rows of w to the first 13 rows in w′ , whereas the remaining rows of w are mapped in blocks of 60, 60, and 59 to the last 3 rows in w′ .…”
Section: Methodsmentioning
confidence: 99%